Clinical and morphological approaches to the differential diagnosis of diphtheric colitis - V. A. Tsinserling; E. I. Belinskaya; V. V. Svistunov (Журнал инфектологии)
Inflammatory bowel diseases is a large group of nosologic forms such as more frequent acute intestinal infection, especially dysentery, chronic inflammatory diseases such as ulcerative colitis and Cron’s disease with lesions of the bowel, antibiotics-associated and ischemic colitis. There are some difficulties in differential diagnostics of inflammatory bowel diseases despite their widespread and tendency to more frequent occurrence. On the one hand, this is largely due to similar clinical picture which is most often presented by diarrhea and abdominal pain of different degree of intensity, and, on the other hand, by the disadvantages of laboratory diagnostics techniques. The article discusses the problem of clinical and morphological aspects of the differential colitis diagnostics with more detailed characteristics of fibrinous colitis of different etiology. The morphological differential diagnostics criteria, as well as a summary table of comparative characteristics of antibiotics-associated pseudomembranous colitis, dysentery, invasive candidiasis of bowel, ulcerative colitis and ischemic colitis have been presented. The importance of an integrated approach to the differential diagnostics of inflammatory bowel diseases, based on the analysis of anamnesis, clinical-laboratory and morphological data is stressed. The algorithm for optimizing of differential diagnostics of inflammatory bowel diseases with recommendations for qualitative morphological examination has been suggested.